The Effects of Various Types of Press Wheels Mounted on Pneumatic Precise Drilling Machine on the Quality Criteria of Black Carrot - Hüseyin Bülbül; Haydar Hacıseferoğulları (International Journal of Secondary Metabolite)
Black carrots are consumed as fresh vegetables in Turkey and are preferred in the form of fermented beverages in large quantities. Black carrots are cultivated in different regions of Turkey. The black carrot is cultivated heavily in the Eregli region. In this region, the highest yields for black carrots are obtained by planting on the ridge at narrow interval range with triplet drilling. In this study, the effects of front and rear stainless steel press wheel (BT1), front and rear rubber press wheel (BT2) and front and rear rubber press wheel and triple narrow intermediate rubber wheels (BT3) on black carrot quality criteria in field conditions were investigated. According to results, yield, single carrot mass, diameter and length varied between, 15.11 and 41.61 t ha-1, 76.96 and 226.43 g, 33.61 and 53.14 mm, and 193.65 and 237.33 mm respectively. It was found that total phenolic varied between 349.80 and 745.37 mg gallic acid equivalent (100 ml)-1 and the antioxidant activity value, determined by DPPH, varied between 26.71% and 54.80%.